Contract bargaining with symmetric information - MacLeod, WB; Malcomson, J (Wiley, 1995)
This paper reviews a recent literature that extends the Rubinstein/Stahl bargaining model to the case of contract bargaining. Theoretical issues, such as the appropriate game form, existence, and uniqueness of equilibria, are discussed. The paper finishes with a brief overview of some applications of the framework.